Yoga intervention as a promising approach to improve quality of life for 21-60 years people with HIV: a literature review - Anak Agung Gede Angga Puspa Negara (Physical Therapy Journal of Indonesia, 2023)
Background: Human immunodeficiency virus (HIV) prevalence is a critical challenge for global public health systems. People living with HIV (PLHIV) experience a variety of physical, mental, and social difficulties that can have a negative influence on their overall quality of life. Yoga, for example, has received attention for its potential to increase well-being in people living with HIV. This review of the literature investigates the effect of yoga intervention on the quality of life of PLHIV aged 21 to 60 years old. Methods: This study employed library research, which drew on online scientific literature about the influence of yoga intervention on the quality of life of PLHIV aged 21 to 60. Six relevant papers demonstrating the beneficial effects of yoga on PLHIV were discovered in the review. Results: When compared to control groups, yoga therapies significantly improved physical well-being, mental health, social functioning, and emotional well-being. Yoga's holistic and integrative nature, which included physical postures, breathing exercises, and meditation, helped PLHIV reduce stress, increase mood, and promote psychological well-being. Yoga benefits include increased physical fitness, flexibility, and a sense of community and togetherness. Conclusion: Yoga intervention has the potential to improve the quality of life and overall health of PLHIV. Yoga can improve well-being and coping mechanisms when incorporated into HIV management plans.